Customer support for the web-based configuration of individualised products. (13th January 2006) - Stegmann, Rosmary; Leckner, Thomas; Koch, Michael; Schlichter, Johann
The main task of mass customisation is the integration of the individual customer's input into the manufacturer's system of value creation. This function can be supported through information technology, such as web-based configurator tools. With such tools customers are enabled to virtually assemble a product. However, customers must also learn to deal with the complexity of the product model and of the configurator tool itself. This work introduces different approaches to overcome the problems of complexity and uncertainty associated with this customer tool interaction. Additionally, the prototype of a web-based configurator tool for products with many degrees of freedom is described from the user's point of view.